ENHANCING COMPETITIVENESS AND QUALITY OF LIFE IN DESTINATIONS THROUGH FEMALE ENTREPRENEURSHIP - Schiemann, Julia; Philipp, Julian; Zehren, Hannah; Schwing, Madlen (The European Journal of Applied Economics, 2023)
To stay competitive, destinations require frequent adaptation and transformation. One trend that has emerged in the early 21st century is the integration of the location, destination and living spaces. One example is the proposed "Ecosystem of Hospitality" that includes aspects such as quality of life, culture, resilience or entrepreneurship. Entrepreneurial activity has the potential to contribute to local and regional economic development. Business foundations in creative markets such as education, fashion, medicine, arts and entertainment may positively impact both residents (living space) and visitors (destination space). As female entrepreneurs are perceived as particularly active in these markets and are often considered to establish more adaptable, resilient, sustainable and transformation-oriented startups, they have great potential to contribute to the competitiveness of destinations and enhance the quality of life for residents and visitors. As a connection of these fields has not been investigated yet, this paper investigates possible correlations between female entrepreneurship and destinations' competitiveness and quality of life. Secondary data from a variety of sources have been analyzed. The findings enhance the linkage between destination development and local entrepreneurship and provide new perspectives for destination managers. Hence, the study contributes to the understanding of the role of female entrepreneurs.
Keywords: Ecosystem of Hospitality, Destination Competitiveness, Quality of Life, Female Entrepreneurship